Identificación de los insecticidas utilizados en el cultivo de cebolla (Allium cepa, Linneo), en la Comunidad El Aguacate, Parroquia Monte Olivo, Cantón Bolívar, Provincia del Carchi, 2017 - Valverde Enríquez, Jorge Luis (2018)
SUMMARY The research was carried out in the community "El Aguacate", located in the parish of Monte Olivo, Cantón Bolívar, province of Carchi, at 2300msnm, in order to know the insecticides that are applied for the control of pests in the onion crop. The primary information was taken, through interviews with the onion producers, who sow for more than 25 years. They preferably cultivate Yellow Granex and Burguesa varieties, because they present resistance to different fungi. The cultural and chemical management to prevent and control pests, is done for: Trips (Thrips tabaci), Cutting Caterpillars (Agrotis ípsilon) and Seed Borer (Delia platura). The attacks of these pests and the phenology of the crop where the damage is more severe were verified in the field. It was also identified that the insecticides most applied in crops are: Spinosad for the control of thrips, apply it 20%, followed by Chlorpyrifos, Profenofos, Chlorpyrifos + Cypermethrin by 33%, 16% of farmers use Methomil, Thiocyclan, 10% use the insecticide, Lambdacyhalothrin + Thiamethoxan, Imidacloprid, and 20% use Benfuracarb, Cypermethrin, Dimethoate, among others; being the most used Spinosad, marketed as Tracer, for its high percentage of effectiveness in all states of the insect. The application of the pesticide is done according to the stage of the crop and the pest to be controlled, the presence or degree of affectation is not monitored, and the frequency of application varies with the weather, reaching an average of 8 to 15 days, in order not to generate resistance; The last application is made 10 days before harvest.